2018
DOI: 10.2308/jfir-52335
|View full text |Cite
|
Sign up to set email alerts
|

Investors' Responses to Reported Earnings when Management Issues Goal versus Expectation Earnings Guidance: An Experimental Investigation

Abstract: We investigate whether nonprofessional investors' responses to a company's reported earnings differ when management earnings guidance is presented as a goal or an expectation. We present 64 M.B.A. students and 262 MTurk participants with earnings guidance, manipulating between subjects whether management provides the guidance as a “goal” or an “expectation” and whether the company's reported earnings fall short or exceed investors' expectations as derived from management's earnings guidance. Our experimental r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Second, different for investors’knowledge in describing an attribution of management earnings guidance information, which it will bring about different evaluation. Hirst et al (1999), Libby et al ( 2006 ), Han and Tan ( 2007 ) and Fanning ( 2018 ) demonstrated that the effects of guidance forms are contingent on investor’ knowledge, only high-knowledge investors are more confident in their earnings estimation, rather than that low-knowledge investors. Third, the material case in this experimental setting not be identified and measured about good news versus bad news of management earnings guidance and macroeconomics information, 12 so they are possible that uncontrolled differences between investors’ perseption in which give to respon imperfect and less sophisticated.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Second, different for investors’knowledge in describing an attribution of management earnings guidance information, which it will bring about different evaluation. Hirst et al (1999), Libby et al ( 2006 ), Han and Tan ( 2007 ) and Fanning ( 2018 ) demonstrated that the effects of guidance forms are contingent on investor’ knowledge, only high-knowledge investors are more confident in their earnings estimation, rather than that low-knowledge investors. Third, the material case in this experimental setting not be identified and measured about good news versus bad news of management earnings guidance and macroeconomics information, 12 so they are possible that uncontrolled differences between investors’ perseption in which give to respon imperfect and less sophisticated.…”
Section: Discussionmentioning
confidence: 99%
“…To develop the next study, it is necessary to consider those attributions especially the ones related to bad news forecast. Some possibilities to develop future research are to consider the form of management earnings guidance information as the research conducted by Han and Tan ( 2007 ) and Fanning et al ( 2018 ). Furthermore, there are still some more dimensions of multiple reference points can be tested by future studies (Baginski et al 2004 ), as an example (Internal: product/service issues/actions/real activity of strategy, organizational issues; External: general economic/environmental issues, governmental, recession/inflation; Future information: analys forecast, financial forecast and so on).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations